Analisis Digital Media Ethnography terhadap Tantangan Akademik dan Sosial-Ekonomi Mahasiswa atas Pembelajaran di Masa Pandemi Covid-19 - Muzakki, Akh (The Sociology of Islam, 2021)
The Covid-19 pandemic has expanded from just a health problem to also a social, economic and educational matter. This article examines the impact of the Covid-19 pandemic on the psycho-academic and socio-economic resilience of students at the same time. Students' combinative resilience to the two broad ranges of problems relies on their different responses to challenges of online learning during the pandemic period. By means of digital media ethnography over the substance of the materials presented by students in their own creative work of pamphlets produced as a final assignment for the Sociology of Education course in the so-called “even semester” of the 20019/2020 academic year, this article argues that the Covid-19 pandemic has had diverse impacts relating not only with the health dimension, but also with psycho-academic and socio-economic one in a combination. It further finds that the Covid-19 pandemic has given rise to psychological pressures along with socio-economic anxieties due to the academic-socio-economic strains faced by students in taking online learning during the pandemic. It also goes on to find that psychological pressures and socio-economic anxieties resulting from the ongoing pandemic of the Covid-19 have manifested themselves together in the form of saturation and a fairly high level of fatigue as well as a decrease in the socio-financial resilience of students during the online learning.